Perencanaan Penjualan Dan Persediaan Optimal Di PT. Interyasa Sedaya Medan - Emita Sri Ulina Surbakti; Kamil Mustafa; Maruli Banjarnahor (Universitas Medan Area, 2018)
Based on development, the enterprise often gets problem in stock of goods, because has not planning for sales and stock of goodsfor the future accuratelly.Method which be used to determine the quantity of sales for the future is “least Square Line Method” because this method is more significance to the result that be hoped and there is also the past data quantitatively. Stock of goods are determined from the quantity of sales for the future with economic order quantity = EOQ.Based on the result of the research that has been done, where the goods that will be are television and refrigerator with the long one month. Increasing of Total sales for TV = 28.7 %. EOQ of TV = 18 units/ order and is performed 1 (one) time is week. Increasing of Total sales for refrigerator = 32.2 %. EOQ of refrigerator = 16 units/ order and is performed 1 (one) time is week.